Inside Cover: Lignin‐Derived Thioacidolysis Dimers: Reevaluation, New Products, Authentication, and Quantification (ChemSusChem 5/2017). Issue 5 (7th March 2017) - Yue, Fengxia; Lu, Fachuang; Regner, Matt; Sun, Runcang; Ralph, John
Abstract : The Inside Cover picture shows the set of 12 newly synthesized, authenticated, and quantified thioacidolysis dimers released from a schematic guaiacyl lignin polymer showing the parent structures flanked by the cleavable β‐ether units in cyan. Such dimers, quantified here for the first time, reflect the distribution of recalcitrant lignin units. Most had not been previously validated, one was previously misassigned and its correction resolves an analytical quandary, and important new β—β dimers have now been identified resolving the long‐standing dilemma that they could not be found in softwood lignin analyses. More details can be found in the Communication by Yue et al. onpage 830 in Issue 5, 2017 (DOI:10.1002/cssc.201700101 ).